Russian Views of Pushkin's Eugene Onegin (Indiana University Press, 1988)
Alexander Pushkin's dazzling poetic masterpiece, Eugene Onegin (1823-1831), occupies a unique place in the history of Russian culture, regarded as the national epic as well as the cornerstone of the nineteenth-century Russian novel. Onegin is so central to Russian culture that generations of Russians have been on intimate terms with its characters, its form, and its flavor, and, from the time of its publication until the present, every important critical movement or literary theory has addressed it. Yet, because the poem's literary qualities are exceptionally difficult to convey in translation, Onegin is little known among non-Russians. This anthology, presenting in English the most influential nineteenth- and twentieth-century criticism devoted to Onegin, offers English-speaking readers an appreciation of the poem's hold on the Russian imagination while illuminating the history of Russian criticism itself.